Extracellular ATP is a pro-angiogenic factor for pulmonary artery vasa vasorum endothelial cells - Gerasimovskaya, Evgenia V. (Springer Netherlands, 2007)
Expansion of the vasa vasorum network has been observed in a variety of systemic and pulmonary vascular diseases. We recently reported that a marked expansion of the vasa vasorum network occurs in the pulmonary artery adventitia of chronically hypoxic calves. Since hypoxia has been shown to stimulate ATP release from both vascular resident as well as circulatory blood cells, these studies were undertaken to determine if extracellular ATP exerts angiogenic effects on isolated vasa vasorum endothelial cells (VVEC) and/or if it augments the effects of other angiogenic factors (VEGF and basic FGF) known to be present in the hypoxic microenvironment. We found that extracellular ATP dramatically increases DNA synthesis, migration, and rearrangement into tube-like networks on Matrigel in VVEC, but not in pulmonary artery (MPAEC) or aortic (AOEC) endothelial cells obtained from the same animals. Extracellular ATP potentiated the effects of both VEGF and bFGF to stimulate DNA synthesis in VVEC but not in MPAEC and AOEC. Analysis of purine and pyrimidine nucleotides revealed that ATP, ADP and MeSADP were the most potent in stimulating mitogenic responses in VVEC, indicating the involvement of the family of P2Y1-like purinergic receptors. Using pharmacological inhibitors, Western blot analysis, and Phosphatidylinositol-3 kinase (PI3K) in vitro kinase assays, we found that PI3K/Akt/mTOR and ERK1/2 play a critical role in mediating the extracellular ATP-induced mitogenic and migratory responses in VVEC. However, PI3K/Akt and mTOR/p70S6K do not significantly contribute to extracellular ATP-induced tube formation on Matrigel. Our studies indicate that VVEC, isolated from the sites of active angiogenesis, exhibit distinct functional responses to ATP, compared to endothelial cells derived from large pulmonary or systemic vessels. Collectively, our data support the idea that extracellular ATP participates in the expansion of the vasa vasorum that can be observed in hypoxic conditions.